10 Hip Abductor Strength In Individuals With Gluteal Tendinopathy: A Cross-sectional Study. (5th September 2014) - Allison, Kim; Bennell, Kim; Vicenzino, Bill; Grimaldi, Alison; Wrigley, Tim; Hodges, Paul
Abstract : Introduction: Gluteal tendinopathy (GT) is a prevalent, debilitating musculoskeletal disease characterised by lateral hip pain at or around the region of the greater trochanter. The condition involves tendinopathic change of the gluteus medius and/or gluteus minimus tendons [Lesquene 2008]. The gluteus medius and minimus muscles act as abductors of the hip. In GT, it is proposed that altered muscle activation patterns and excessive hip adduction in function can result in compression of the gluteal tendons against the greater trochanter, resulting in pathological tendon changes [Cook 2012]. Despite this widely held conviction and the derivation of conservative treatment programs based on this premise addressing hip abductor strength, there have been no studies to date investigating hip abductor strength in this population compared to controls. The aim of this study was to evaluate maximal isometric hip abductor strength in individuals with GT compared to healthy asymptomatic controls (AC). Methods: A cross-sectional study: 23 individuals (5 males, 18 females) with unilateral MRI confirmed GT and 23 age- (within 2 years) and gender-matched AC's were recruited. Control symptomatic' and 'asymptomatic' hips were designated by matching sides (left or right) to that of their GT pair. Leg dominance (defined as the leg used to kick a ball) was noted. Isometric hip abduction strength was measured on both sides in supine (gravity-eliminated), in a position of ten degrees hip abduction. Measurement of maximal force was recorded in Newtons using a dynamometer placed above the lateral malleoli; the distance from the dynamometer to the greater trochanter (D) was recorded in metres. Three maximal attempts of a three second isometric abduction contraction were recorded, with a 60 second rest between efforts. The highest recorded value was used (with the value D) to calculate maximal isometric abduction torque, normalised to body mass (Nm/kg). Levels of lateral hip pain were self-reported using a numeric rating scale (0–10 with 10 being maximal pain) during strength testing, as well as day-to-day average pain, worst pain and duration of symptoms. Participants reported whether pain prevented them from pushing as hard as they could (pain inhibition). Data were analysed using a one-way ANOVA, and subsequently using an ANCOVA with covariates of pain levels, pain inhibition and leg dominance. Correlation analysis was performed using Spearman's Rho to assess the relationship between abduction strength and duration of symptoms and average pain. Results: The average duration of symptoms in the GT group was 31.2 (37.5) months. The GT group reported their day-to-day average lateral hip pain as 4.8 (0.8), worst pain experienced as 7.5 (1.3), and pain during testing as 3.0 (2.0). Eighteen of the 23 GT participants experienced pain during testing and 7 reported pain inhibition. When using pain inhibition, pain during testing and leg dominance as covariates, the GT group demonstrated significantly reduced hip abductor torque of both their symptomatic leg (p < 0.001) and of their asymptomatic leg (p = 0.024) when compared to the control group (Table 1 ). There was no significant correlation between symptomatic hip abductor strength and duration of symptoms (r =-0.32, p = 0.13) or symptomatic hip abductor strength and average pain (r = 0.13, p = 0.55). Discussion: Individuals with GT demonstrated significantly reduced hip abductor strength bilaterally when compared to ACs. Patients in the GT group experienced only low levels of pain during isometric hip abduction, consistent with the rationale for isometric exercise prescription in tendinopathy. Electromyographic and biomechanical investigation in this population will provide further information regarding the potential relationship of hip abductor strength on functional hip adduction control and abductor muscle recruitment. References: Lesquene et al . Arth Rheumatism 2008;59:241–246 Cook et al . Br J Sports Med 2012;46:163–168